2014
DOI: 10.3390/nu6125392
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Usage of Dietary Supplements in Patients by Miscommunication with Physicians in Japan

Abstract: Recently, people have used dietary supplements not only for nutritional supplementation, but also for treatment of their diseases. However, use of dietary supplements to treat diseases, especially with medications, may cause health problems in patients. In this study, we investigated use of dietary supplements in patients in Japan. This survey was conducted from January to December 2012, and was completed by 2732 people, including 599 admitted patients, 1154 ambulatory patients, and 979 healthy subjects who at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 37 publications
(35 reference statements)
1
61
1
3
Order By: Relevance
“…We previously surveyed dietary supplement usage in patients in Japan and found that some had been concomitantly taking dietary supplements and medicines 12) . However, approximately 70% of these patients did not declare the use of dietary supplements to their physicians 12) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously surveyed dietary supplement usage in patients in Japan and found that some had been concomitantly taking dietary supplements and medicines 12) . However, approximately 70% of these patients did not declare the use of dietary supplements to their physicians 12) .…”
Section: Discussionmentioning
confidence: 99%
“…However, approximately 70% of these patients did not declare the use of dietary supplements to their physicians 12) . Therefore, health issues caused by interactions between dietary supplements and drugs may occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some consumers expect such food products to have effects similar to those of drugs (Chiba et al, 2014b). However, some consumers expect such food products to have effects similar to those of drugs (Chiba et al, 2014b).…”
Section: Current Issues In Foods With Health Claimsmentioning
confidence: 99%
“…Consumers are highly motivated to take advantage of such functionalities in an effort to improve and maintain health and, in some cases, to prevent disease (Chiba et al, 2014b). Recent developments in food science and technology have revealed various physiological functionalities in foods and food components.…”
Section: Introductionmentioning
confidence: 99%